The Effect of Learning Media Based on Geogebra Software on Mathematics Learning Results on Straight Line Equations - Mandira, Firsta Ayu; Wahyuni, Sri (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine whether there is an effect of GeoGebra software-based learning media on mathematics learning outcomes in straight line equations and whether there is an increase in learning using GeoGebra media. This research was conducted at MTs PAB 1 Helvetia with 27 students in class VIII-A as the experimental class. This study uses a one group pretest posttest design. Students are given tests to measure student learning outcomes. From the results of the study, the average pretest score was 45.3704 and the posttest average was 75,000. The t value at the significant level = 0.05, the t_table value is 1.708. Then t_count (15.872) > t_table (1.708). So, it can be concluded that Ho is rejected and Ha is accepted. The conclusion of this study explains that there is an influence of the GeoGebra Software learning media on mathematics learning outcomes where there is an increase in the average value of learning outcomes after being taught using GeoGebra Software learning media